„Das tragischste Kapitel deutscher Wanderungsgeschichte der Nachkriegszeit“: Das Scheitern des deutschen Migrations- und Siedlungsprojekts bei La Serena, Chile, in den 1950er Jahren - Villarroel, Tomas (Anuario de Historia de América Latina, 2018)
The article presents a failed plan of emigration of German colonists to Chile during the first half of the 50’s. Previous scholarship has explored the organization and development of this agricultural project. Here we add reflection on the ways in which the post-war upheavals, and the problem of European displacements, affected the relation between Germany and Chile during this period. There has been no previous attempt to explain the impact of the cold war on this remote place, but it is worthy of consideration from both the German and Chilean point of view. The project broke down, though, in light of national interests of both states. Even though the soil was bad, President González Videla held fast to the project, given the prestige involved. On the other hand, the workers that had been elected for this purpose were hardly prepared. Problems with the language, inadequate professions, as well as the conduct of the colonists, made the project enormously difficult. It is hard to resist the impression that the German government intended to get rid of a part of its own population coming from the east-European area, which was considered hard to integrate. The return of the expatriates is a significant illustration of the end of long-term circulation between the eastern-European, the western-European, and the transatlantic world, and also of the end of transatlantic European migration to South America.